Effect of mobile application use on knowledge about human immunodeficiency virus among university students - Soares, Yndiara Kássia da Cunha (2022)
OBJECTIVE: To evaluate the effect of using a mobile application on knowledge about human immunodeficiency virus among university students. METHOD: A before-and-after intervention study, with 196 university students, from August to December 2018. The intervention consisted of using the educ@aids mobile application for 15 days. Univariate analyzes were performed using simple descriptive statistics and the McNemar test was used to compare knowledge before and after the intervention. RESULTS: There was an improvement in knowledge after using educ@aids in the variables related to knowledge about the transmission of the virus; knowledge about treatment, cure and prevention; knowledge of other information about human immunodeficiency virus. CONCLUSION: The use of educ@aids increased knowledge about the human immunodeficiency virus among health university students.